KONSELING KELOMPOK DENGAN PENDEKATAN EKLEKTIK UNTUK MENURUNKAN TINGKAT STRESS PADA PESERTA DIDIK KORBAN BULLYING - Khairunisa Khairunisa; Neviyarni Neviyarni; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
This study aims to determine the effect of group counseling services using an eclectic approach to post-bullying stress in SMA Negeri 4 Medan students in the 2021/2022 academic year. This research is a quantitative research with a quasi-experimental design with the type of Pre-test-post-test group design. The subjects in this study were 10 students of class XI MIA SMA Negeri 4 Medan who had a high level of post-bullying stress. Subjects were taken using a screening method with a purposive technique. The research data were collected using a valid and reliable questionnaire. Data were analyzed using the Wilcoxon test. From the data analysis, it was obtained that J count = 0 with = 0.05, while J table = 8. From these data it can be seen that Jcount < JTable where 0 < 8. This means that the hypothesis is accepted. Post-test data after being given the eclectic approach group counseling service obtained an average of 47.9, the difference between the pretest and posttest was 31.8 and the change in the post-bullying stress interval for students after being given the eclectic approach group counseling service was 39.89%. This means that the average score of students who have a high level of post-bullying stress after receiving an eclectic approach group counseling service is lower than before receiving an eclectic approach group counseling service. This shows that there is an influence of an eclectic approach group counseling service on students who have stress levels. high post-bullying or the hypothesis can be accepted.